General line-line method for propagation constant measurement of non-reciprocal networks. (15th August 2022) - Hasar, Ugur Cem; Ozturk, Hamdullah; Korkmaz, Huseyin; Izginli, Mucahit; Karaaslan, Muharrem; Bute, Musa
Abstract: A general "line-line" (LL) method is proposed for propagation constant determination ( γ + and γ − ) of nonreciprocal networks using multiple reference networks. The new formalism provides flexibility in implementation of LL methods so that not only more accurate γ + (and γ − ) could be retrieved but also the effect of inaccurate length information of the non-reciprocal network on γ + (and γ − ) evaluation could be suppressed. For validation of the method, γ + and γ − of a microwave phase shifter (a nonreciprocal network) are determined using uncalibrated scattering parameter measurements at X-band (8.2–12.4 GHz). Two different statistical analyses based on normalized root-mean-square-error and goodness of fit and based on coefficient of variation and confidence interval are individually performed to evaluate the performance and accuracy of our method. Highlights: A new methodology is proposed to evaluate propagation constant of non-reciprocal networks. It has the capability of improving the measurement accuracy (reducing the uncertainties). It can reduce the effect of inaccurate length information of non-reciprocal line/networks.